The Prevalence of Transfusion-Transmitted Infections and Their Associated Risk Factors Among Transfusion-Dependent Beta-Thalassemia Major Patients Registered in a Tertiary Care Hospital in Jamnagar, Gujarat - Parmar, Alpesh; Shah, Viral; Patel, Harsh; Patel, Bela (International Journal of Innovative Research in Medical Science, 2023)
Background: Thalassemia is an inherited disease. Thalassemia major patients are transfusion-dependent and are very much prone to transfusion-transmitted viral infections. So, this study was conducted to determine the prevalence and various determinants, contributing in blood transfusion transmitted infection among them. Methodology: A 12-month longitudinal research on thalassemia major patients who met the inclusion criteria and were registered in the thalassemia ward of a tertiary care institution was undertaken from December 2021 to November 2022. Information regarding Transfusion transmitted infection was collected. Result: This study was applied to a total of 222 thalassemia major patients. The prevalence of Hepatitis C infection found to be 51 (22.97%) followed by HIV 5 (2.25%) and hepatitis B infection was found in one patient (0.45%). When various parameters were compared to Transfusion transmitted infection, only history of splenectomy and place of diagnoses were shown to be substantially related to the TTIs (p < 0.05), whereas all other factors were statistically insignificant (p > 0.05). Conclusion: Our findings reveled that HCV is the most common TTI among thalassemia major patients followed by HIV and HBV. Patients who were splenectomized and diagnosed from private hospital were more prone to Transfusion transmitted infection.